Fear and Experience of Childbirth among Primiparous Women - Pokhrel, Prajnya; Bharati, Mamata; Bhandari, Sushila (Journal of Nepal Health Research Council, 2024)
Background: The fear of childbirth is the feeling of fearfulness, anxiety or worry among women in relation to pregnancy and childbirth process which influence their experience of childbirth which is the subjective feeling of sadness or joyfulness regarding childbirth. The main objective of the study was to identify the relationship between fear and experience of childbirth among primiparous women.Methods: A descriptive cross-sectional study was done where non probability, purposive sampling technique was used to select a sample of 133 primiparous women attending Paropakar Maternity and Woman’s Hospital having term pregnancy (37-42 weeks of gestation) without any complications and willing to participate in the study. Data were collected through interview technique. Fear of childbirth was assessed by using standard Wijma Delivery Expectancy/ Experience Questionnaire (WDEQ) and experience of childbirth was assessed by using Childbirth Experiences Questionnaire (CEQ). Data analysis was done by using descriptive statistics like frequency, mean, percentage and standard deviation and inferential statistics i.e. Pearson’s correlation and chi square test in Statistical Package for Social Sciences version 16.Results: The study revealed that fear and experience of childbirth were negatively correlated (r= -0.254). The majority of the respondents (64.7%) had a moderate level of fear of childbirth. Most of the respondents (80.5%) had a positive experience of childbirth. Conclusions: This study concludes that there is negative relationship between the fear of childbirth and its experience. Women having higher fear of childbirth have less positive experience of childbirth. Keywords: Childbirth; experience of childbirth; fear of childbirth; mode of delivery.